Studi kelayakan bisnis pada peternakan kambing Bagong Farm Pacitan - Pratopo, Gentur (Maliki Interdisciplinary Journal, 2024)
The Bagong Farm livestock business was founded in 2019 by Mr. Prapto and his son Reza Taufik Wicaksono, whose address is at Dukuh Prambon, Sukoharjo Village, District. Pacitan Regency. Pacitan. The Bagong Farm Pacitan goat farming business carries out business activities that involve raising and managing goats to obtain products and services from these animals such as meat, milk and leather as crafts. Apart from that, Bagong Farm also provides a special type of contest goat. The Bagong Farm goat farming business is feasible. Based on the feasibility analysis of technical aspects, the business owner has good goat care skills, namely by providing food, maintaining health, and cleaning the cage and livestock. The human resource aspect of managing the business is also sufficient to run this micro-scale business. Environmentally and socio-culturally, this business can provide an example of entrepreneurial practice to the surrounding community. Goat dung can be used as organic fertilizer and compost for surrounding farms. However, in terms of licensing, Bagong Farm still does not have an official permit such as NIB.